Evidence of collaboration, pooling of resources, learning and role blurring in interprofessional healthcare teams: a realist synthesis. Issue 1 (January 2015) - Sims, Sarah; Hewitt, Gillian; Harris, Ruth
Abstract Interprofessional teamwork has become an integral feature of healthcare delivery in a wide range of conditions and services in many countries. Many assumptions are made in healthcare literature and policy about how interprofessional teams function and about the outcomes of interprofessional teamwork. Realist synthesis is an approach to reviewing research evidence on complex interventions which seeks to explore these assumptions. It does this by unpacking the mechanisms of an intervention, exploring the contexts which trigger or deactivate them and connecting these contexts and mechanisms to their subsequent outcomes. This is the second in a series of four papers reporting a realist synthesis of interprofessional teamworking. The paper discusses four of the 13 mechanisms identified in the synthesis: collaboration and coordination; pooling of resources; individual learning; and role blurring. These mechanisms together capture the day-to-day functioning of teams and the dependence of that on members' understanding each others' skills and knowledge and learning from them. This synthesis found empirical evidence to support all four mechanisms, which tentatively suggests that collaboration, pooling, learning, and role blurring are all underlying processes of interprofessional teamwork. However, the supporting evidence for individual learning was relatively weak, therefore there may be assumptions made about learning within healthcare literature and policy that are not founded upon strong empirical evidence. There is a need for more robust research on individual learning to further understand its relationship with interprofessional teamworking in healthcare.